キショウ エイセイ NOAA データ ショリ ソウチ - 高部, 広昭; タカベ, ヒロアキ; 山内, 恭; ヤマノウチ, タカシ; Takabe, Hiroaki; Yamanouchi, Takashi (1989)
P(論文) 第28次南極地域観測隊では, 気象衛星NOAAデータ処理装置を昭和基地(69°00′S, 39°35′E)に搬入, 運用を始めた。これは, 1987年から始まった「南極域における気候変動に関する総合研究(Antarctic Climate Research : ACR)」の中で, 衛星画像データの処理を通じて広域の雲や海氷分布を求めるためのものである。FACOM S3300ミニコンピューターを中心としたシステムで, 受信データをリアルタイムに取り込み, キャリブレーションを行うことでアルベドや温度に変換し, 投影変換を行い, 結果を画像表示し, また磁気テープに保存する。その他, 雪氷面上の雲識別方法の検討を行うため, 輝度温度差画像やヒストグラムを作成した。 The 28th Japanese Antarctic Research Expedition has installed a NOAA data processing system at Syowa Station (69°00′S, 39°35′E) and has started the operation. This system is used to obtain cloud and sea ice distribution in the broad area under the project of "Antarctic Climate Research (ACR)", which started in 1987. The main part of the system is composed of a FACOM S3300 mini computer, which is used to acquire the received data of satellite at a real time, to make the calibration to obtain the albedo and temperature, to make a map projection, to display the images and to store the data in computer compatible tapes. Moreover, images of brightness temperature difference and histogram are made to discuss the way to discriminate clouds over the snow and ice surfaces. departmental bulletin paper